Nuclear Transmutations and Low Energy Nuclear Reactions at the Unitary Quantum Theory (Global Journal of Science Frontier Research, 2014)
In this article is discussed problems Low Energy Nuclear Reactions -with position unitary quantum theory. Probability of these phenomena more than predicts usual quantum theory for small energy.
Keywords: unitary quantum theory; cold nuclear fusion; low energy nuclear reactions; coulomb repulsion; quantum mechanics; coulomb barrier; nuclear transmutatio